Detection of Apoptotic Cells in Human Colorectal Cancer by Two Different in situ Methods: Antibody against Single‐stranded DNA and Terminal Deoxynucleotidyl Transferase‐mediated dUTP‐biotin Nick End‐labeling (TUNEL) Methods - Ichizo Watanabe; Masao Toyoda; Junji Okuda; Toshiyuki Tenjo; Keitaro Tanaka; Tetsuhisa Yamamoto; Hiroshi Kawasaki; Toshihiro Sugiyama; Yoshihiko Kawarada; Nobuhiko Tanigawa (1999)
Wecomparatively investigated the extent of apoptotic cell loss in human colorectal cancers evaluated by two methods, namely the conventional terminal deoxynucleotidyl transferase (TdT)‐ mediated deoxyuridine triphosphate (dUTP)‐biotin nick end‐labeling (TUNEL) method and immunohistochemistry for single‐stranded (ss) DNA. The apoptotic index (AI) obtained with the TUNEL method was higher than that shown by the immunohistochemistry for ssDNA. However, a significant correlation in AIs evaluated by these methods was found. The AIs obtained by both methods were significantly higher in the advanced cancers than in the early cancers. Cellular proliferation activity was assessed in terms of positivity rate (PR) for expression of proliferating cell nuclear antigen (PCNA). The PR of advanced cancers was significantly higher than that of early cancers. The present results indicate that immunohistochemistry for ssDNA is useful (as is the TUNEL method) for evaluation of apoptotic tumor cells in colorectal carcinomas. In addition, it was confirmed that there is a remarkable increase of not only proliferation activity, but also tumor cell apoptosis in the process of progression of colon cancer from early to advanced stages of the disease.